The Economic Prospects of the Chicken Slaughterhouse Industry in Residential Environments - Rajab, Ridwan; Rivai, Firman Hadi; Suhartono, Bambang (KnE Social Sciences, 2022)
The activity of the chicken slaughterhouse industry has a significant impact on the community’s socioeconomic conditions; and various changes in economic activity have opened up opportunities for the community’s industrial businesses to grow, particularly in the livestock sector. The growth of community economic activities in the livestock sector, particularly in the chicken slaughterhouse industry as a home industry with a business location in a residential area, has created its own set of challenges. The purpose of this study was to describe community perceptions, collaboration among poultry industry stakeholders, and Government policies regarding the presence of a chicken slaughterhouse home industry in the middle of a residential neighborhood in the context of local community economic development. The study was carried out using qualitative descriptive methods. Interviews, focus groups, observations, and documentation analysis were used to gather information and the inductive approach was used to analyze the data. The researchers gathered data on citizens, businesses, and Government perceptions. The study’s research locus was Makassar City’s chicken slaughterhouse industry, with Serang City and Bogor City serving as comparison loci. The findings revealed that the residential chicken slaughterhouse industry is a traditional micro-scale operation. These businesses have both advantages and disadvantages because, on the one hand, they have the potential to cause environmental and health problems, but as a local business, they also have the potential to support the local economy. It was found that the development of the chicken slaughterhouse home industry has resulted in numerous positive benefits for the community, both economically and socially, such that the positive impacts outweigh the negative impacts. According to the findings, the Government should develop a policy that protects residents’ business activities while minimizing their negative impact. It is critical for the Government to return to reviewing licensing policies and community empowerment, especially given the Government’s difficulties in implementing economic recovery for the community, particularly in dealing with unemployment and other social issues. Keywords: chicken slaughterhouse home industry, local community economy, local government policies